Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas V SDN 3 Anjir Mambulau Timur Kecamatan Kapuas pada Mata Pelajaran IPA dengan Menggunakan Metode Pembelajaran Doubel Loop Problem Solving (DLPS) dan Media Audio Visual Tahun Pelajaran 2016/2017 - Raymullah Rahman; Chandra Anugrah Putra (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims: (1) To describe the learning activities of fifth grade students of SDN-3 Anjir Mambulau Timur on science subjects using the Double Loop Problem Solving (DLPS) and Audio Visual Media methods, and, (2) To determine the improvement in learning outcomes Science using the Double Loop Problem Solving (DLPS) Method and Audio Visual Media. To the fifth grade students of Anjir Mambulau East SDN-3 2016/2017 academic year. The research method used in this study is the Classroom Action Research (CAR) method. Determination subjects were class V students of SDN-3 Anjir Mambulau Timur with a total of 13 students consisting of 5 men and eight women. Data analysis techniques used qualitative and quantitative. From the results of the study concluded that: (1) Learning activities of fifth-grade students of SDN-3 Anjir Mambulau Timur by using the Double Loop Problem Solving (DLPS) Method and Audio Visual Media. In science subjects, it is better. This is evidenced from the average results in the observational data on the activities of students in the first cycle, which is 2.87 increased to 3.3 in the second cycle, (2) There is an increase in science learning outcomes using the Double Loop Problem Solving (DLPS) and Media Method Audiovisual. This can be seen from the acquisition of the average value of each cycle increasing. In the first cycle obtained an average cost of 71 and classical completeness 84% included in the criteria not achieved and in the second cycle increased to 77 and 100% artistic completeness including the tests achieved